Tren dan Strategi Pengembangan Publikasi Ilmiah Nasional dan Internasional Bidang Hadis dan Ilmu Hadis - Idri, Idri; Arif, Mohammad (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
This article aims to explain the trends in national and international scientific publications in the field of hadith and hadith science in Indonesia, both in terms of publishing journals and articles published in those journals. Essentially, the study material in scientific publications in the field of hadith and hadith science, both nationally and internationally, can be viewed from two perspectives: riwayah studies and dirayah studies. Both have their own trends, although dirayah studies are more widely published in national and international journals. To further develop scientific publications in the field of hadith and hadith science, it is important to pay attention to current trends in Indonesian scientific publications. This should be developed using strategies proposed by experts, including those proposed in this study. All obstacles, especially internal and external ones, must be overcome through various means, involving relevant parties.